Relating the construction and maintenance of maternal ill-health in rural Indonesia - Lucia D'Ambruoso (Taylor & Francis Group, 2012)
Estimates suggest that over 350,000 deaths and more than 20 million severe disabilities result from the complications of pregnancy, childbirth or its management each year. Death and disability occur predominately among disadvantaged women in resource-poor settings and are largely preventable with adequate delivery care. This paper presents the substantive findings and policy implications from a programme of PhD research, of which the overarching objective was to assess quality of, and access to, care in obstetric emergencies. Three critical incident audits were conducted in two rural districts on Java, Indonesia: a confidential enquiry, a verbal autopsy survey, and a community-based review. The studies examined cases of maternal mortality and severe morbidity from the perspectives of local service users and health providers. A range of inter-related determining factors was identified. When unexpected delivery complications occurred, women and families were often uninformed, unprepared, found care unavailable, unaffordable, and many relied on traditional providers. Midwives in villages made important contributions by stabilising women and facilitating referrals but were often scarce in remote areas and lacked sufficient clinical competencies and payment incentives to treat the poor. Emergency transport was often unavailable and private transport was unreliable and incurred costs. In facilities, there was a reluctance to admit poorer women and those accepted were often admitted to ill-equipped, under-staffed wards. As a result, referrals between hospitals were also common. Otherwise, social health insurance, designed to reduce financial barriers, was particularly problematic, constraining quality and access within and outside facilities. Health workers and service users provided rich and explicit assessments of care and outcomes. These were used to develop a conceptual model in which quality and access are conceived of as social processes, observable through experience and reflective of the broader relationships between individuals and health systems. According to this model, differential quality and access can become both socially legitimate (imposed by structural arrangements) and socially legitimised (reciprocally maintained through the actions of individuals). This interpretation suggests that in a context of commodified care provision, adverse obstetric outcomes will occur and recur for disadvantaged women. Health system reform should focus on the unintended effects of market-based service provision to exclude those without the ability to pay for delivery care directly.